PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN PERUBAHAN WUJUD BENDA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDI LASIANA - Welmi A. N. Pandie; Gaspar Melo; Maxsel Koro (Universitas Nusa Cendana, 2023)
This study aims to improve student learning outcomes in learning about themes. 3 things around me sub-theme 3 Changes in the form of learning objects first, in class 3 SDI Lasiana, with the discovery learning model. this type of research is classroom action research is an examination of learning activities in the form of action, which are deliberately raised and occur in a class together, with the following stages: planning, implementation, observation, and reflection. by selecting the SD Inpres Lasiana, Kupang, grade 3 location. the subjects of this study were 25 grade 3 students. data collection was done through observation and testing techniques. the results of the study in the first cycle of the class average value of 60.2 increased to 81.4 in the second cycle, with an increase in the average value from cycle I to cycle II of 21.2. The percentage of classical learning completeness in the first cycle, which was 44%, increased to 92% in the second cycle, with an increase in the percentage of 48%. student activity in cycle I was 62.66 and increased to 80.3 in cycle II, an increase of 17.64. It can be concluded that the application of the discovery learning model in learning about theme 3 things around me sub-theme 3 changes in the form of learning objects 1 can help students in SDI Lasiana Kupang city's class 3 achieve better results